Reducing whole of enterprise running costs through coarse particle flotation - Graeme Jameson (International Mineral Processing Congress, 2014)
"In current flotation circuits it is customary to grind the whole of the mill feed to an initial size, which is determined by the liberation characteristics of the ore, and the ability of the flotation machines to float the fully liberated particles. Usually, the product of the primary mill will be ground further in a ball mill, to improve the liberation of the values and hence the product grade, before passing to rougher flotation cells. The final grind size is ore-dependent, and is a balance of factors including the relation between surface liberation and grind size, the grain size of the valuable particles within the host rock, and the feed grade. The P80 for the feed to flotation may be as high as 300 µm for free-milling copper ores, and as low as 53 µm for finely disseminated complex ores. The grinding of the feed ore requires considerable input of energy. The rate of replacement of wear components such as mill liners and media, is proportional to the energy input. The costs of these two factors - energy and wear - are usually comparable and together they form the major part of the running costs of a concentrator, and indeed, of the whole mining operation. The energy required increases as the final grind size decreases. This talk will focus on the reduction of milling costs that could be achieved, using a fluidized bed flotation technology that can give high recoveries at coarse particle sizes. A number of different circuit designs will be presented, using the new technology. Calculations show that reductions in the running costs of a mine and associated concentrator of the order of ten to twenty percent could be achieved."